Association between Interleukin-10-1082 G/A and Tumor Necrosis Factor-α 308 G/A Gene Polymorphisms and Respiratory Distress Syndrome in Iranian Preterm Infants - Abolfazl Khoshdel; Soleiman Kheiri; Peyman Omidvari; Fahimeh Moradi; Majid Hamidi; Hossein Teimori (Mediators of Inflammation)
Cytokine polymorphisms may contribute to the prevalence of respiratory distress syndrome. The present study was done to investigate the frequency of interleukin- (IL-) 10 and tumor necrosis factor- (TNF-) α gene polymorphisms and their association with the risk of RDS in preterm infants. One-hundred and nineteen patients with RDS and 119 healthy preterm infants were enrolled. PCR restriction fragment length polymorphism was used to determine the frequency of IL-10 and TNF-α genotypes at -1082 A and -308 A, respectively. One-hundred and nineteen out of 238 infants had RDS (50%). The age of the mothers and gestational age ranged 17–45 (mean: 28.6±5.3) years and 24–34 (mean: 34.3±2.38) weeks, respectively. Totally, 23 deaths were recorded in the RDS group. Incidence of TNF-α-308 A/A and TNF-α-308 G/A was 84% and 16%, respectively. TNF-a-308 G/G was not found in both groups. Prevalence of IL-10-1082 G/G and IL-10-1082 G/A variants was 65.5% and 34.5%, respectively. IL-10-1082 A/A was not found in both groups. The incidence of the allele G in the IL-10-1082 polymorphism was lower in RDS group (P<0.05). We found that the risk of RDS was correlated to sex, gestational age, and IL-10-1082.